From Stream to Cart: Investigating the Role of Parasocial Interaction and Local Presence on The Urge to Buy Impulsively in Live-Streaming Shopping - Vidyanata, Deandra (Jurnal Aplikasi Manajemen, 2025)
Despite the importance of Parasocial Interaction and Local Presence as characteristics of live-streaming shopping, these constructs have not yet been thoroughly explored in the literature. Thus, this study aims to investigate the underlying mechanism by which the Urge to Buy Impulsively can be formed through the mediation of Utilitarian Value. This is interesting because the study seeks to determine whether Utilitarian Value can rationalize the occurrence of impulsive behavior in the live-streaming context. Using purposive sampling, an empirical study tested the model with an online survey of 450 Shopee Live-Streaming users. This study found that Parasocial Interaction and Local Presence directly affect Urge to Buy Impulsively. Parasocial Interaction directly affects Utilitarian Value, but Local Presence does not. Furthermore, Utilitarian Value was found to have a significant negative effect on Urge to Buy Impulsively. For indirect effects, Utilitarian Value mediates the effect of Parasocial Interaction on Urge to Buy Impulsively. Conversely, Utilitarian Value fails to mediate the effects of Local Presence and Urge to Buy Impulsively. Thus, in live-streaming shopping, marketers should prioritize engaging hosts who can form a virtual connection with the viewers, as this increases both the Urge to Buy Impulsively and the Utilitarian Value of products. Additionally, presenting virtual products as they appear in the viewers’ real environment is important to drive the Urge to Buy Impulsively. However, marketers should be cautious about overemphasizing the utilitarian aspects of a product if the goal is to drive impulsive purchases, as this may reduce the impulsive urge to buy.